2019
DOI: 10.1536/ihj.19-054
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Moderate or More Residual Regurgitation in Patients with Moderate Chronic Ischemic Mitral Regurgitation Undergoing Surgical Revascularization Alone

Abstract: Few reports have focused on which patients with moderate ischemic mitral regurgitation (IMR) were not good candidates for coronary artery bypass grafting (CABG) alone. This single-center study aimed to assess risk factors for moderate or more residual regurgitation within two years after CABG alone for the treatment of moderate chronic IMR to optimize the operation strategy and prognosis. A total of 189 eligible patients were entered into a failure group (n = 108) or an improved group (n = 81) according to whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 29 publications
(49 reference statements)
2
10
0
Order By: Relevance
“…In a recent meta‐analysis 21 in patients with moderate IMR with or without mitral valve (MV) repair or replacement the incidence of moderate‐to‐severe MR at follow‐up was higher in the coronary artery bypass grafting alone group (risk ratio, 3.24; 95% confidence interval, 1.79‐5.89; P < .001). The same findings were confirmed by other studies on moderate IMR 3,22‐24 …”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…In a recent meta‐analysis 21 in patients with moderate IMR with or without mitral valve (MV) repair or replacement the incidence of moderate‐to‐severe MR at follow‐up was higher in the coronary artery bypass grafting alone group (risk ratio, 3.24; 95% confidence interval, 1.79‐5.89; P < .001). The same findings were confirmed by other studies on moderate IMR 3,22‐24 …”
Section: Introductionsupporting
confidence: 88%
“…The same findings were confirmed by other studies on moderate IMR. 3,[22][23][24] Similar studies on MR secondary to aortic valvulopathies showed that, after aortic valve replacement, both transfemoral and surgical, preoperative MR was a risk factor for higher mortality [25][26][27][28][29][30][31] or heart failure 28,29,32 during the follow-up, in particular, if ejection fraction was less than 50% 33 or, in general, low. 32 Other studies found that the patients at risk were those where MR did not reduce but persisted or worsened after either procedure.…”
Section: Introductionmentioning
confidence: 76%
“…The approach to ischemic MR of moderate degree in patients undergoing CABG remains controversial [Michler 2016;Smith 2014]. Although CABG may be able to eliminate moderate MR in selected patients, if reverse LV remodeling by viable myocardium, which affects papillary muscle geometry, does not occur, MR seems to remain [Salmasi 2018;Ji 2019;Penicka 2009]. In this condition, a mild degree of MR often is overlooked when CABG is performed.…”
Section: Discussionmentioning
confidence: 99%
“…Michler 1 analyzes the different aspects of the disease in terms of IMR grade, LV dysfunction and remodeling, presence of LV scars, and quality of the coronary circulation to give an opinion on how to drive the surgical correction according to IMR severity. While restrictive mitral annuloplasty (RMA) remains a valid surgical option for moderate IMR in presence of LV enlargement, poor coronary targets, or baseline inferior–posterior–lateral wall motion abnormalities, as reported by others, 7 in the author's opinion, overcorrective RMA does not benefit severe IMR, as it can exacerbate leaflet tethering. RMA could require complementary ventricular surgical procedures such as papillary muscle (PM) approximation.…”
mentioning
confidence: 90%